The European Central Bank's QE: A New Hope - Tomasz Wieladek; Antonio I. Garcia Pascual (Center for Economic Studies and ifo Institute (CESifo), 2016)
We examine the impact of the ECB's QE on Euro Area real GDP and core CPI with a Bayesian VAR, estimated on monthly data from 2012M6 to 2016M4. We assess the total impact via a counter-factual exercise, country-by-country and through alternative transmission channels. QE anouncement shocks are identified with four different identification schemes as in Weale and Wieladek (2016). We find that in absence of the first round of ECB QE, real GDP and core CPI would have been 1.3% and 0.9% lower, respectively. The effect is roughly 2/3 times smaller than in the UK/US. Impulse response analysis suggests that the policy is transmitted via the portfolio rebalancing, the signalling, credit easing and exchange rate channels. Spanish real GDP benefited the most and Italian the least.
Keywords: E50; E51; E52; 330; ECB unconventional monetary policy; transmission mechanism